Successful treatment of anastomotic jejunal varices with N-butyl-2-cyanoacrylate (Histoacryl): single-center experience - Gubler, C.; Glenck, M.; Pfammatter, T.; Bauerfeind, P. (Endoscopy, 2012)
Obscure gastrointestinal bleeding can lead to extensive diagnostic work-up, as well as repeated episodes of hospitalizations with significant morbidity. Patients with a previous small-bowel anastomosis seem to be prone to varices at this site, even in the absence of portal hypertension. We report here five cases with varices of this type. All the anastomoses in these patients were reached using overtube-assisted single- or double-balloon enteroscopy. The bleeding varices were treated by injecting N-butyl-2-cyanoacrylate (Histoacryl). Bleeding was stopped in all five patients without any adverse events, requiring one session in four patients and a second session in one patient.